Manual do Cuidador - Manuel Veríssimo (Outros Títulos, 2019)
The Caregiver's Handbook for "Active and Healthy Aging - Guidelines for Better Management in Health and Disease" is divided into 6 modules: The caregiver - what role does it play; Caring for the other (structurin knowledge); The interdisciplinary pillars (doctor, caregiver and technology); The caregiver - what to know about the health and rights of the elderly; Take care of yourself and end with the sharing of Life Stories (caregiver experiences). The themes emphasize the interdisciplinarity necessary to know the aging process, which allows a complete formation in this area highlighting the imporance of the individual, society, lifestyle choices and the understanding of aging in the biological, psychological and health context for the optimization of the life course that provides strategies to ptevent frailty, physical and cognitive decline. The acquisition of skills in the communication between integrated clinical services, caregivers and health professionals and, in the caregiver module, the knowledge of how to help treat the elderly with altered mobility, lodging, diabetes, cognitive deficit / dementia, chronic pathology, pain, malnutrition and sleep disturbances are goals that we intend to achieve.